CALOGENESIS IN DIFFERENT CUTTINGS OF JAPANESE PERSIMMON TREATED WITH CHILL AND INDOLBUTIRIC ACID - Silva, Ivo Ditos da; Faquim, Rudival; Carvalho, Ruy Inacio Neiva de (Scientia Agraria, 2006)
The objective of this work was to evaluate the influence of collection date, chill treatment and doses of indolbutiric acid (IBA) in the calogenesis in cuttings of ‘Fuyu’ japanese persimmon. The japanese persimmon tree presents different intensity of bud dormancy during the autumn and winter, then the cellular growth needed to the calogenesis is influenced by the season and the chill occurence, and both can determine the cell hability to respond the auxins action. The branches were collected in August, 8th (hardwood cuttings) and February, 2nd (semi-hardwood cuttings) and, in each date, 50 % of branches were treated with 504 hours of chill (4 to 7° C) and the remaining branches were used to prepare the witch were then submitted to differents dosis of IBA (0, 1,000, 2,000 and 3,000 mg L-1). The velocity of budburst was determined and after 60 days the percentage of cuttings with callus, sprouted, dorment and dead were evaluated. The calogenesis occured in 20.83 % of the semi-hardwood cuttings without the chill treatment. There was not calogenesis in the hardwood cuttings. In the semi-hardwood cuttings, the velocity of budburst was smaller than the hardwood cuttings, however the last one presented 90.04 % of mortality. The IBA treatment do not influenced the calogenesis. The calogenesis was stimulated in the semi-hardwood cuttings without chill treatment. The budburst velocity was more intense in the hardwood cuttings treated with chill. The chill treatment induced the dormancy of buds in the semi-hardwood cuttings. The mortality was bigger in the hardwood cuttings treated with chill.